2022
DOI: 10.1001/jamanetworkopen.2022.36738
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk of Rheumatoid Arthritis Among Underground Hard Rock and Other Mining Industry Workers in Colorado, New Mexico, and Utah

Abstract: ImportanceRespirable silica exposure has been strongly and consistently linked to rheumatoid arthritis (RA) among foundry workers, persons in the construction trades, stone crushers and drillers, and coal miners. However, risk of RA in hard rock mining has not been thoroughly investigated.ObjectiveTo analyze occupational risk of RA in hard rock miners in Colorado, New Mexico, and Utah.Design, Setting, and ParticipantsThis cross-sectional survey study estimated the association between mining industry work and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Blanc et al showed that miners and individuals exposed to hard rock mining activities had nearly four times the risk of RA. 36 Interestingly, miners were also at risk of other non-RA arthritides, underlining that dust exposure has a holistic effect on the immune system. Similarly, soldiers exposed to burn pits had a greater touchREVIEWS in RMD risk of presenting ACPA-positive RA.…”
Section: Chronic Exposure and Risk Of Rheumatic Musculoskeletal Diseasesmentioning
confidence: 99%
“…Blanc et al showed that miners and individuals exposed to hard rock mining activities had nearly four times the risk of RA. 36 Interestingly, miners were also at risk of other non-RA arthritides, underlining that dust exposure has a holistic effect on the immune system. Similarly, soldiers exposed to burn pits had a greater touchREVIEWS in RMD risk of presenting ACPA-positive RA.…”
Section: Chronic Exposure and Risk Of Rheumatic Musculoskeletal Diseasesmentioning
confidence: 99%
“…Crystalline silica is a common component of the earth’s crust and sand. Occupational exposure occurs mainly in the construction and stone-working industries [ 2 , 3 ]. When respirable crystalline silica is inhaled, it can trigger inflammatory processes and the production of reactive oxygen species, which can lead to fibrogenesis and carcinogenesis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Blanc et al had recently published, in JAMA Network Open, a cross-sectional study aimed to test the hypothesis that hard rock mining is associated with greater risk of RA. 7 The authors surveyed, telephonically, nearly 2000 men from the southwest of the USA, a region characterised by elevated incidence of pneumoconiosis. The questionnaire covered countless aspects of the lifestyle and working habits as well as medical history and medications.…”
mentioning
confidence: 99%